إستخدام كتاب" المقصود " لترقية فهم القواعد الصرفية فى الصف الثالث المدرسة الدينية في المعهد تربية الناشئين باجول جوانج جومبانج - Khofifatus Sa’adah; Lailatul Qomariyah (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
Kitab al-Maqshud is an important reference in learning Arabic morphology (sharaf) at Ma’had Tarbiyatun Nasyi’in. This book covers word structure changes in Arabic, such as from singular to plural, masculine to feminine, as well as rules of wazn and verb classification. This study aims to analyze the use of Kitab al-Maqshud in the third-year madrasah diniyah, assess students’ mastery of morphology rules, and identify supporting and hindering factors in the learning process. A descriptive qualitative method was used, involving observation, interviews, and documentation. The results show that the book is taught using bandongan and sorogan methods, combining memorization, comprehension, and direct practice. Its use has improved students’ ability to distinguish verb forms, apply wazn rules, and boosted their confidence in using Arabic. Supporting factors include teacher attentiveness, a supportive learning environment, and varied methods such as games and discussions. Main obstacles are students' varying abilities, limited time, and the complexity of the material, which requires repetition. Overall, al-Maqshud remains a relevant and effective resource when delivered with appropriate and flexible teaching methods.